Prediction of high performance in sports and games based on genetic analysis - Kamath, R.; Vishwanath, B. S. (Journal of Physical Education & Sports Science, 2020)
Champions are born with inherited physical potential, and by providing all kinds of support like technical, psychological, environmental, they can be molded into top class performers. Individuals have always been screened through different means for their athletic, physical and behavioral prowess that contributes to their high performance in sports. There has been a variety of screening methods like Pre-Participation Physical Evaluation (PPE) to screen for illnesses, injury susceptibility or medical conditions. Counseling has always been done to understand the psychological aspect of the athletes. This has been a mandatory administrative requirement for sports authorities/federation for organized sports for years. However, the main drawback to these screening methods have always been that it was time-consuming, non-uniformity of protocols, compliance issues and occasionally no follow-up is done. With all these existing conventional screening procedures, if the athlete does not possesses their required inherited potentialities any form of support will result in identifying/developing an average athlete.